Border Security and Herdsmen Terrorism in Northern Nigeria: A Call for A New National Security Policy - Omojowo, Sunday; Oyekanmi, Abiodun; Samuel, Salako Anuoluwapo (Indonesian Journal of Political Studies, 2025)
Strengthened security architecture of any nation is dependent on the ability to ensure safe and well-defined borders. Border security is central to national security as the first line of defence against threats. In Nigeria, borders are sources of the unending insecurity, being one of the most porous in Africa. Thus, the study, descriptive in nature, examined border security and herdsmen terrorism in northern Nigeria. It adopted securitisation theory as its theoretical framework and relied heavily on secondary data. The study argued that Nigeria’s borders are susceptible to criminal infiltration due to poor management. This had heightened ruthless killings and destruction of properties by herdsmen in northern Nigeria. The borders, demarcated by expired tires, blocks, and sticks, are manned by unqualified, inadequately equipped, and corrupt personnel and allow herdsmen terrorists to constantly enjoy free movement into the nation, becoming a threat to security, peace, and stability. The study concluded that if Nigeria’s borders are not securitised as a high priority, state authority will be weakened and sovereignty will wane continuously. The study therefore recommended that borders should be properly policed with adequate provisions for advanced surveillance technology installed at all border areas, and international cooperation should be encouraged in the fight against herdsmen terrorism.